Combined effect of skeletal muscle mass loss and elevated insulin resistance on heart failure risk in older adults: a community-based longitudinal cohort study - Weike Liu; Hua Zhang; Xin Wang; Huajing Song; Yanli Yao; Zhendong Liu; Juan Wang; Yuqi Guo (Cardiovascular Diabetology)
Abstract Background Skeletal muscle mass loss and insulin resistance (IR) are associated with cardiovascular diseases risk. However, it remains unclear whether the combination of skeletal muscle mass loss and elevated IR affects heart failure (HF) risk. Here, we investigate the association between a combination of appendicular skeletal muscle mass index (ASMI) with estimated glucose disposal rate (eGDR) and HF risk in older adults. Methods A prospective analysis and a dual-trajectory analysis were carried out to investigate the association of the combined effect of ASMI and eGDR with HF risk. A total of 11,596 adults aged ≥ 60 years were enrolled from the community for prospective analysis. Among them, 10,489 were eligible for the dual-trajectory analysis. The temporal evolution of ASMI and eGDR was determined using a dual-trajectory model. Results In the prospective analysis, 1087 individuals developed HF. Restricted cubic splines analysis showed L-shaped associations between ASMI and eGDR and HF risk. HF risk decreased by 32.3% (hazard ratio (HR): 0.677, 95% confidence interval (CI): 0.623–0.734, P adj < 0.001) for female and 9.0% (HR 0.910, 95% CI 0.831–0.996, P adj = 0.003) for male patients per one standard deviation (SD) AMSI increment and 29.4% (HR 0.706, 95% CI 0.647–0.770, P adj < 0.001) for female and 26.8% (HR 0.732, 95% CI 0.668–0.803, P adj < 0.001) for male patients per one SD eGDR increment. There was a synergistic effect on HF risk per one SD ASMI and eGDR increment (P adj < 0.001). Five distinct dual ASMI and eGDR trajectories were identified in the dual-trajectory analysis. A total of 859 (8.85 per 1000 person-years) individuals developed HF. Compared to group 4 with moderate-stable ASMI and eGDR and the lowest incident HF, the HR in group 5 characterized by low-stable ASMI and eGDR was 1.908 (95% CI 1.482–2.457, P adj < 0.001), followed by 1.716 (95% CI 1.296–2.273, P adj < 0.001) in group 3 with low-decrease ASMI and high-decrease eGDR. Conclusions Skeletal muscle mass loss and elevated IR act synergistically to increase the HF risk in older adults. Comprehensive management of muscle mass and IR might be a useful and effective strategy for preventing and controlling HF. Trial registration Retrospectively registered number ChiCTREOC17013598.